Caffeine and contraction synergistically stimulate 5′‐AMP‐activated protein kinase and insulin‐independent glucose transport in rat skeletal muscle. Issue 10 (14th October 2015) - Tsuda, Satoshi; Egawa, Tatsuro; Kitani, Kazuto; Oshima, Rieko; Ma, Xiao; Hayashi, Tatsuya
Abstract: 5′‐Adenosine monophosphate‐activated protein kinase (AMPK) has been identified as a key mediator of contraction‐stimulated insulin‐independent glucose transport in skeletal muscle. Caffeine acutely stimulates AMPK in resting skeletal muscle, but it is unknown whether caffeine affects AMPK in contracting muscle. Isolated rat epitrochlearis muscle was preincubated and then incubated in the absence or presence of 3 mmol/L caffeine for 30 or 120 min. Electrical stimulation (ES) was used to evoke tetanic contractions during the last 10 min of the incubation period. The combination of caffeine plus contraction had additive effects on AMPK α Thr 172 phosphorylation, α ‐isoform‐specific AMPK activity, and 3‐ O ‐methylglucose (3MG) transport. In contrast, caffeine inhibited basal and contraction‐stimulated Akt Ser 473 phosphorylation. Caffeine significantly delayed muscle fatigue during contraction, and the combination of caffeine and contraction additively decreased ATP and phosphocreatine contents. Caffeine did not affect resting tension. Next, rats were given an intraperitoneal injection of caffeine (60 mg/kg body weight) or saline, and the extensor digitorum longus muscle was dissected 15 min later. ES of the sciatic nerve was performed to evoke tetanic contractions for 5 min before dissection. Similar to the findings from isolated muscles incubated in vitro, the combination of caffeine plus contraction in vivo had additive effects on AMPK phosphorylation, AMPK activity, and 3MG transport. Caffeine also inhibited basal and contraction‐stimulated Akt phosphorylation in vivo. These findings suggest that caffeine and contraction synergistically stimulate AMPK activity and insulin‐independent glucose transport, at least in part by decreasing muscle fatigue and thereby promoting energy consumption during contraction. Abstract : We found that using rat skeletal muscle, caffeine and contraction synergistically stimulate 5′‐adenosine monophosphate‐activated protein kinase activity and insulin‐independent glucose transport, at least in part by decreasing muscle fatigue and thereby promoting energy consumption during contraction.